Advanced nursing practice in reproductive planning - Intrauterine device insertion: An experience report - Oliveira Dias, Cristiano Leonardo; Martins Silva, Yan Lucas (Nursing Edição Brasileira, 2022)
Objective: to report the experience of nurses in the placement of intrauterine devices (IUD) within the scope of advanced nursing practices. Method: this is an experience report based on the experiences of nurses, in a specialized outpatient clinic, in the city of Belo Horizonte (MG), during the periods from November 2021 to April 2022. Results: the completion of training for the placement of IUDs favored the application of differentiated care, entirely based on scientific evidence. During the consultation, the difficulty in carrying out the procedures became evident, especially in view of the occurrence of adverse reactions in the patients. In view of this, one of the professionals in training even developed an instrument that would assist in cutting the IUD threads, after being inserted into the woman’s uterus. expand the scope of professional nursing practice.